Integration effects in border regions: A survey of economic theory and empirical studies - Annekatrin Niebuhr; Silvia Stiller (Hamburg Institute of International Economics (HWWA), 2002)
Border regions and border effects currently attract a lot of attention in political practice and economic research. Substantial interest in regions located along the frontiers of integrating countries is predominantly inspired by the presumption that their specific geographic position might cause peculiarities in economic adjustments to integration. This survey explores whether economic theory and empirical studies support the assessment that integration effects concentrate in border regions. Economic theory alone allows only very vague conclusions about the spatial effects of integration. Depending on specific circumstances, border regions might benefit, lose or not be affected by integration. Empirical research on border regions – undertaken so far - does not allow to draw clearcut conclusions as well. At present, there is neither a direct test for integration effects in border regions, nor a comprehensive study on the development of border regions. To sum up, the survey suggests that rigorous theoretical and empirical analysis is needed to foster the understanding of integration effects in border regions. – – Grenzregionen und Grenzeffekte ziehen in der politischen Praxis und in der wirtschaftswissenschaftlichen Forschung gegenwärtig großes Interesse auf sich. Ursächlich hierfür ist die Vermutung, dass die besondere geografische Lage von Grenzregionen spezifische ökonomische Integrationseffekte bedingt. Dieser Überblick fasst die Ergebnisse der ökonomischen Theorie und empirischer Untersuchungen zu dieser Fragestellung zusammen. Es ist festzustellen, dass die ökonomische Theorie keine eindeutigen Schlussfolgerungen erlaubt. Ob Grenzregionen von Integration profitieren, negativ beeinflusst werden oder unberührt bleiben, hängt von den konkreten Gegebenheiten ab. Auch die vorliegenden empirischen Studien zu Grenzregionen gelangen zu keinen eindeutigen Resultaten. Bisher gibt es allerdings weder eine direkte Überprüfung der Integrationseffekte in Grenzregionen noch umfassende Untersuchungen der wirtschaftlichen Entwicklung von Grenzregionen. Insgesamt zeigt dieser Überblick, dass weitergehende theoretische und empirische Untersuchungen erforderlich sind, um fundierte Kenntnisse über Integrationseffekte in Grenzregionen zu erlangen.
Keywords: R12; F15; O18; 330; regional development; border regions; integration effects; Grenzgebiet; Wirtschaftsintegration; Marktintegration; Regionale Entwicklung; Theorie; Welt